A Note on the Valuation of a CDO and of an nth-to-Default CDS Without Monte Carlo Simulation - Boyer, Martin; Marquis, Olivier (Assurances et gestion des risques / Insurance and Risk Management, 2009)
The quasi-closed form solution to estimate default probabilities for a group of n assets developped in Hull and White (2004) allows a bypass of traditional Monte-Carlo simulations to value credit default swaps and collateralized debt obligations. The authors then construct a simple example to illustrate their approach. The purpose of the present note is to raise the issue that the closed form solution presented does not yield the empirical results of the simple example. Finally, we show how the two can be reconciled.